Analisis dan Optimalisasi Akses Point To Point Menggunakan Perangkat Power Beam M5 400 Out Dor Sistem (Studi Kasus : Onesnet) - Rasim .; Mugiarso (LPPM STMIK IKMI Cirebon, 2022)
Onesnet is a home internet service provider or what is called RT / RW Net so to provide this service Onesnet sends signals or data to remote areas using point-to-point access points and because the client itself is disseminated again, with that we use devices access point Nano Station Power Beam M5. This paper aims to implement point-to-point access and optimize two NanoStation M5 devices without using additional antennas to improve the quality and coverage of a wireless local area network, to obtain further coverage. The design was carried out at Onesnet Housing Mustika Karangsatria Blok EA 18 Number 3A, with a maximum radius of 1000 meters, with received signal strength parameters, ping test, and connection quality, as well as path losses using the Friis propagation model. By using the test results there are no obstacles or line of sight (LOS), it is proven that the access point device can reach a range of up to 1000 meters, and from the site survey test results, it is concluded that the observation location is in good connection quality to very good quality, the average is in a radius of fewer than 1000 meters from the access point. While the observation locations with poor connection quality are on average outside 1000 meters from the access point, and several locations cannot connect at all because the received signal is too weak..